A Cross-Level Holistic Model Of Public Service Motivation. Issue 5 (20th October 2018) - Liu, Bangcheng; Perry, James L.; Tan, Xinyu; Zhou, Xiaohua
ABSTRACT: Using a sample of 63 supervisors and their direct reports (189 immediate subordinates), this study investigated a cross-level model of public service motivation's (PSM) antecedents in the Chinese public sector. Correlation analyses and hierarchical linear modeling (HLM) results simultaneously revealed that both subordinates' proactive personality and supervisors' servant leadership were related positively to subordinates' PSM. Additionally, HLM analyses demonstrated that supervisors' servant leadership and their immediate subordinates' proactive personality interacted to correlate positively with subordinates' PSM. Implications of the findings, limitations, and directions for future research are discussed.